Environmental Regulations and Rules: United Nations Perspective and the Nigeria Experience - FASHUYI OLUGBENGA (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
This research reviewed Nigeria’s environmental laws within the context of Agenda 21 at the three levels of water, forest degradation and solid waste management with the intent of evaluating the importance of Agenda 21 on environmental sustainability in the country. Furthermore, the study examined Nigeria’s environmental laws to determine its effectiveness. In this way, the study provided information on the effectiveness and extent of United Nations interventions on environmental issues in Nigeria thereby revealing the gap between such interventions and actual environmental challenges of the country.